1990
DOI: 10.1016/1044-0305(90)80009-c
|View full text |Cite
|
Sign up to set email alerts
|

Charge-remote fragmentation in a hybrid (BEqQ) mass spectrometer to determine isotopic purity in selectively polydeuterated surfactants

Abstract: The combination of fast atom bombardment with charge-remote fragmentation using a hybrid (BEqQ) mass spectrometer was used successfully to assess and localize the extent of selective deuterium isotope labeling of tetradecyItrimethylammonium bromides. Spectral details reveal a new reaction that can give rise to ions isobaric with those formed by chargeremote fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…However, we only observed an ion at m/z 304, which we attributed to the cetylpyridinium ion, reflecting loss of the chloride ion. This finding is in agreement with fast‐atom bombardment (FAB) mass spectrometric studies, e.g., by Tuinman et al ,14 in which the spectra of similar cationic surfactants were dominated by ions due to the pre‐formed cations. In order to confirm our mass assignment, we prepared separate MALDI samples using commercial standards of cetylpyridium bromide and cetylpyridinium chloride.…”
Section: Resultssupporting
confidence: 92%
“…However, we only observed an ion at m/z 304, which we attributed to the cetylpyridinium ion, reflecting loss of the chloride ion. This finding is in agreement with fast‐atom bombardment (FAB) mass spectrometric studies, e.g., by Tuinman et al ,14 in which the spectra of similar cationic surfactants were dominated by ions due to the pre‐formed cations. In order to confirm our mass assignment, we prepared separate MALDI samples using commercial standards of cetylpyridium bromide and cetylpyridinium chloride.…”
Section: Resultssupporting
confidence: 92%
“…However, the work of Tuinman et ul. 23.24 on a closely related precursor ion, uiz (C14H2Y)N+(CH3)3r raised questions as to whether or not the fragment ions observed in the present work truly were CRF reaction products. By studying the specifically deuterated ion (C14D2Y)N+(CH3)3, these workers showed that two mechanisms contribute to CID reactions leading to expulsion of the elements of CnHZn+,, formerly regarded as characteristic of CRF reactions.…”
Section: Charge-remote Fragmentations Of Long-chain Tetraalkylammoniumentioning
confidence: 84%
“…6 D, exhibits a peak pattern with a series of intense ions spaced 14 u apart, as reported previously. [18][19][20][21] CID of the [M+H] + cation resulted in a product ion at m/z 267 that was assumed to be derived from the cleavage of an amide bond (Fig. 6 B).…”
Section: Cid Of Amines With Unsaturated Hydrocarbon Chains N-oleoyletmentioning
confidence: 99%